Triangulation: Establishing the Validity of Qualitative Studies - Lisa A. Guion (EDIS, 2002)
This publication is FCS6014, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: September 2002.